The SPS algorithm: patching figural continuity and transparency by Split-Patch Search - Criminisi, Antonio; Blake, Andrew (2004 Computer Vision and Pattern Recognition, 2004)
This paper describes a novel algorithm for the efficient synthesis of high-quality virtual views from only two input images. The emphasis is on the recovery of continuity of objects boundaries (figural continuity) with faithful synthesis of transparency effects. The contribution of this paper is two-fold: (i) the split-patch search (SPS) technique is introduced for dense stereo which handles transparency effects by assigning multiple disparities to mixed pixels; (ii) an efficient extension of exemplar-based image synthesis to the case of two-camera stereo is proposed. Furthermore, this paper presents an approximate but effective solution to the challenging problem of layer estimation and compositing in the case of small image patches. The effectiveness of the proposed technique is demonstrated on a number of stereo image pairs taken from two camera video-conferencing setups, where the quality of the synthesized talking heads is of paramount importance. Moreover the improvement in the quality of image synthesis is quantified by comparing the output of the SPS algorithm with thirteen ground-truth images.